Exploring Multi-Parameter Effects on Iron Oxide Nanoparticle Synthesis by SAXS Analysis - Marco Eigenfeld; Marco Reindl; Xiao Sun; Sebastian P. Schwaminger (Crystals)
Iron oxide nanoparticles (IONs) are extensively used in biomedical applications due to their unique magnetic properties. This study optimized ION synthesis via the co-precipitation method, exploring the impact of the reactant concentrations (Fe(II) and Fe(III)), NaOH concentration, temperature (30 °C–80 °C), stirring speed (0–1000 rpm), and dosing rate (10–600 s) on particle size and growth. Using small-angle X-ray scattering (SAXS), we observed, for example, that higher temperatures (e.g., 67 °C compared with 53 °C) led to a 50% increase in particle size, while the stirring speed and NaOH concentration also influenced nucleation and aggregation. These results provide comprehensive insights into optimizing synthetic conditions for targeted applications in biomedical fields, such as drug delivery and magnetic resonance imaging (MRI), where precise control over nanoparticle size and properties is crucial.